Evaluation report on Revamped Public Distribution System (1993-94) - Planning Commission (Planning Commission Government of India, 1995)
"This document synthesizes the findings of the Evaluation Report on the Revamped Public Distribution System (RPDS) for the period 1991–94, along with subsequent assessments of operational efficiency and financial assistance mechanisms for strengthening the Public Distribution System (PDS) across Indian States and Union Territories. Introduced in 1992, the RPDS sought to improve access to essential commodities for vulnerable populations in economically backward, remote, tribal, and drought-prone regions through expanded coverage, affordable pricing, and decentralized delivery mechanisms. The evaluation highlights notable progress in expanding the network of Fair Price Shops and achieving high distribution levels for staple commodities such as rice and wheat. However, persistent challenges are identified, including inadequate coverage in remote areas, poor storage and transport infrastructure, irregular functioning of FPSs, weak quality control, and ineffective vigilance mechanisms. State-specific analyses reveal significant mismatches between commodity allocation and local consumption preferences, alongside declining purchasing power due to rising issue prices. The report also reviews financial assistance schemes supporting mobile vans and godown construction, emphasizing enhanced subsidies and community-based vigilance committees to improve last-mile delivery and accountability. Overall, the findings underscore the need for localized planning, strengthened infrastructure, robust monitoring systems, and greater community participation to enhance the effectiveness of the RPDS. The study concludes that while the RPDS has contributed to food security for disadvantaged groups, systematic reforms and adaptive implementation strategies are essential to realize its full potential as an instrument of social equity and inclusive development."
Programme Evaluation Organisation Planning Commission Government of India New Delhi 1995
Keywords: Revamped Public Distribution System; Food Security; Fair Price Shops; Vulnerable Populations; Commodity Distribution; Infrastructure Development; Storage and Transport; Vigilance Committees; Financial Assistance Schemes; State-wise Performance; Community Participation; Policy Reforms